DISKRIMINASI YANG DIALAMI ORANG DENGAN HIV/AIDS (ODHA) DAMPINGAN YAYASAN SEHAT PANGHURIPAN SUKOWATI KABUPATEN SRAGEN - DHIFA IFTINAN MAITSA; Admiral Nelson Aritonang; Helly Okctilia (Indonesian Journal of Social Work, 2021)
This research is to determine and understand the discrimination experienced by people living with HIV / AIDS at the Panghuripan Sukowati Health Foundation, Sragen Regency, include: 1) characteristics of the informant, 2) verbal expression, 3) avoidance, 4) exclusion, 5) physical abuse and 6) informant's expectations. The method used in this research is descriptive qualitative. Informants in this study were five (5) people with HIV / AIDS and two (2) foundation manager, the determination of informants is done by using purposive sampling technique. Data collection techniques used were in-depth interviews, observations and documentation studies. Data sources used are primary data sources and secondary data sources. The results showed that verbal insults received by informants in the form of words and sentences were expressed to denigrate people with HIV/AIDS. Avoidance is done by avoiding or keeping away people with HIV/AIDS. Exclusion is done by removing people with HIV/AIDS from a group by terminating social relations. Furthermore, physical abuse is carried out by hurting, beating or attacking people with HIV/AIDS due to their HIV status. The problem of discrimination against people with HIV/AIDS occurs due to stigma against HIV / AIDS and the lack of community acceptance of people with HIV/AIDS. The proposed program is "Increasing Family and Community Concern for People with HIV / AIDS in Efforts to Decrease Discrimination against PLWHA".